Financing irrigation services: a literature review and selected case studies from Asia - Small, L.E.; Adriano, M.S.; Martin, E.D.; Bhatia, R.; Shim, Y.K.; Pradhan, P. (International Irrigation Management Institute, 1989)
This study results from a two years' intensive research into a hitherto unexplored area of irrigation management - the aspect of financing irrigation in some Asian countries. The authors have analyzed the relationship between investment costs, level of irrigation fees, cropping intensity, type of crop, and secondary income. The studies conclude that the quality of irrigation system operations and maintenance is affected not only by the amount of resources made available to operate and maintain systems, but also by the institutional arrangements under which they are provided.